Reforestation and carbon balance of forest ecosystems in the central forest-steppe of the European part of Russia: Challenges and prospects for sustainable development - S. S. Morkovina; E. A. Kolesnichenko; N. V. Yakovenko; S. S. Sheshnitsan; A. N. Vodolazhskiy (Юг России: экология, развитие, 2025)
The aim of the article is to analyse the carbon sequestration potential of forest-climate projects and sustainable development of ecosystems in the conditions of the central forest-steppe of the European part of the Russian Federation.Statistical data on the forest cover of the Belgorod, Voronezh, Kursk, Lipetsk and Tambov Regions, reforestation dynamics, as well as information on climatic and anthropogenic threats have been used in this work. Methods of comparative analysis of forest management measures, ecosystem services assessment and modelling of forest ecosystems contribution to carbon sequestration have been applied. Particular attention was paid to analysing the effectiveness of artificial reforestation.It was found that the forests of the central forest-steppe are characterised by low forest cover (8.6 %), a high proportion of artificial plantations  (30–70 %) and an annual volume of reforestation of up to 3 thousand ha. It was found that the Tambov and Lipetsk Regions demonstrate the highest carbon potential due to more favourable conditions for the growth of plantations. The total carbon dioxide uptake due to reforestation reaches 11.84–20.39 t/ha CO₂-eq. and in 50 years will increase to  120.16–164.34 t/ha CO₂-eq. Climate aridisation and forest fires are the main threats that reduce the effectiveness of classical forest management approaches. Degrading old-growth forests make a minimal contribution to carbon sequestration.The implementation of regional forest-climatic projects with a focus on modernising reforestation and improving ecosystem resilience can significantly increase carbon sequestration and contribute to the development of conservation and production functions of forests.